Traunkirchen with the Spitzelstein in Upper Austria - Kolb, Joseph Maximilian (engraver):::Creator::::::::::::; Lange, Julius (artist):::Contributor:::::::::::: (Mortiz Perles ; Ferdinand Lange; Austria; Vienna)
Engraving of the Traunkirche and Traunsee located in Upper Austria, with the Spitzelstein in the background